2016
DOI: 10.1016/j.rbmo.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Higher β-HCG concentrations and higher birthweights ensue from single vitrified embryo transfers

Abstract: To examine the effect of cryopreservation on developmental potential of human embryos, this study compared quantitative β-HCG concentrations at pregnancy test after IVF-fresh embryo transfer (IVF-ET) with those arising after frozen embryo transfer (FET). It also tracked outcomes of singleton pregnancies resulting from single-embryo transfers that resulted in singleton live births (n = 869; with 417 derived from IVF-ET and 452 from FET). The initial serum β-HCG concentration indicating successful implantation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
1
18
1
Order By: Relevance
“…Whereas the correlation between frozen cycles and LGA is well established, the association with GDM is controversial. Contrary to our findings, Liu et al (2013), Sazonova et al (2012) and Keane et al (2016) reported comparable rates of GDM among singleton pregnancies after fresh and frozen ET. The lack of association between GDM and cryopreservation in previous studies and the weak association found in the current study led us to suspect the association with LGA relates to either the vitrification or the warming process and is not a consequence of GDM.…”
Section: Article In Presscontrasting
confidence: 99%
See 1 more Smart Citation
“…Whereas the correlation between frozen cycles and LGA is well established, the association with GDM is controversial. Contrary to our findings, Liu et al (2013), Sazonova et al (2012) and Keane et al (2016) reported comparable rates of GDM among singleton pregnancies after fresh and frozen ET. The lack of association between GDM and cryopreservation in previous studies and the weak association found in the current study led us to suspect the association with LGA relates to either the vitrification or the warming process and is not a consequence of GDM.…”
Section: Article In Presscontrasting
confidence: 99%
“…Miscarriage rate in our study could be affected by the difference in embryo quality between the two study groups. Higher rates of miscarriage in vitrified-warmed cycles were found by Keane et al (2016) as well. Our finding may be related to the differences in the rate of PCOS between the two groups (16% versus 11%, P = 0.002).…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, LIF can play an important role in influencing endometrial receptivity and maternal-fetal interface during early pregnancy. β-HCG concentration may be applied as an indicator of potential developmental progress of the embryo [21]. In our study, we also found that pregnancy predictions in combination with LIF and β-HCG are significantly better than their individual predictive power.…”
Section: Discussionsupporting
confidence: 62%
“…There was no significant difference in outcomes between both agents. Our FET HRT protocols have been described previously in detail [21]. Briefly, from day 1 to 10 patients received estradiol (E2) valerate (Progynova; Bayer, Reading, UK) tablets (4 mg three times per day) and endometrial thickness was graded on day 10 by a transvaginal ultrasound (TVUS) scan.…”
Section: Clinical Aspects Of Stimulation and Fet/hrt Treatment Cyclesmentioning
confidence: 99%